Flame-retardant expandable polystyrene bead and preparation method thereof

Hyperbranched core-shell flame retardants were prepared by shell coating and hyperbranching of expanded graphite, which solved the flame retardancy and compressive strength problems of expandable polystyrene materials and achieved good flame retardant performance and high compressive strength.

CN121021903AActive Publication Date: 2025-11-28LIAONING LITIAN NEW MATERIAL CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511575422.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-31
Publication Date
2025-11-28
Estimated Expiration
2045-10-31

AI Technical Summary

Technical Problem

Expandable polystyrene is easily combustible at high temperatures, producing toxic gases and molten droplets. Furthermore, the weak interfacial interaction between expanded graphite and polystyrene molecular chains leads to reduced compressive strength, affecting the material's flame retardant properties and mechanical performance.

Method used

Flame-retardant expandable polystyrene beads are prepared by using hyperbranched core-shell flame retardants and by encapsulating and hyperbranching expanded graphite. The diffusion and deformation capabilities of the inner shell layer effectively encapsulate the matrix material, while the outer shell layer enhances the material structure through cross-linking.

Benefits of technology

It improves the flame retardant properties and compressive strength of polystyrene foam, forms a dense and stable network structure, and enhances the bonding strength and integrity of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121021903A_ABST
    Figure CN121021903A_ABST
Patent Text Reader

Abstract

The invention provides a flame-retardant expandable polystyrene bead and a preparation method thereof, and belongs to the technical field of polystyrene beads, the flame-retardant expandable polystyrene bead is prepared from the following raw materials by weight: 20 parts of a styrene monomer, 0.20-0.25 part of an organic dispersant, 0.05-0.15 part of an inorganic dispersant, 0.75-0.85 part of a foaming agent, 3.8-4.2 parts of a hyperbranched core-shell flame retardant, 0.4-0.6 part of an initiator and 90-110 parts of water, wherein the hyperbranched core-shell flame retardant is prepared by carrying out shell coating and hyperbranched treatment on expanded graphite, and the hyperbranched core-shell flame retardant is added in the polystyrene polymerization process, so that the expanded graphite has good compatibility with a polymer matrix, and meanwhile, a matrix material can be effectively coated and protected after high-temperature expansion; the finally prepared polystyrene foam material has good flame retardant property, and can maintain high compressive strength at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of polystyrene beads, and particularly relates to a flame-retardant expandable polystyrene bead and a preparation method thereof. BACKGROUND

[0002] Expandable polystyrene (EPS) is also known as foamed polystyrene, which is a kind of foam material with low cost and excellent performance, can prevent moisture, heat insulation, sound insulation and vibration reduction, has small thermal conductivity and water absorption, and excellent dielectric performance, and is widely used in the fields of filling packaging of articles and energy saving and thermal insulation of buildings.

[0003] Expandable polystyrene beads are white bead-shaped particles containing high-volatility low-boiling-point blowing agents, which are used for foaming and molding to prepare EPS foam materials. EPS foam materials have a large specific surface area and a honeycomb-like cell structure, and are easy to burn at high temperatures, producing toxic gases and molten droplets, which seriously limits their application in many fields. Expanded graphite has expandability and flame retardant performance. When expanded graphite is introduced into a polymer emulsion, the expanded graphite particles can be uniformly dispersed in the polymer matrix as the polymerization reaction proceeds. Compared with conventional mixing, the combination has higher flame retardant efficiency. However, the porous structure formed by the expansion of expanded graphite has poor diffusion and deformation ability, and it is difficult to effectively wrap and protect the foam matrix after expansion, which affects the flame retardant effect. At the same time, the interface interaction between expanded graphite and polystyrene molecular chains is weak, and stress concentration occurs between expanded graphite and polystyrene matrix when subjected to external force, thereby reducing the compressive strength and affecting the overall mechanical properties of the material. SUMMARY

[0004] To solve the problems in the background art, the application provides a flame-retardant expandable polystyrene bead and a preparation method thereof, so that the prepared foamed polystyrene material has good flame retardant performance and can maintain high compressive strength.

[0005] To achieve the above-mentioned purpose, the technical scheme of the application is as follows: A flame-retardant expandable polystyrene bead is prepared from the following raw materials by weight parts: 20 parts of styrene monomer, 0.20-0.25 parts of an organic dispersant, 0.05-0.15 parts of an inorganic dispersant, 0.75-0.85 parts of a blowing agent, 3.8-4.2 parts of an hyperbranched core-shell flame retardant, 0.4-0.6 parts of an initiator, and 90-110 parts of water, wherein the hyperbranched core-shell flame retardant is prepared by shell coating and hyperbranched treatment of expanded graphite. The preparation method of the flame-retardant expandable polystyrene bead comprises the following steps: The raw materials are weighed by mass fraction, the styrene monomer, hyperbranched core-shell flame retardant and deionized water are put into the reaction kettle, mixed uniformly, then half of the amount of inorganic dispersant, half of the amount of organic dispersant and initiator are put in, mechanical stirring for 30-60 min, the temperature of the material in the reaction kettle is raised to 80-90℃, and the polymerization reaction is carried out at this temperature for 6-10 hours; the remaining dispersant and foaming agent are added, the reaction kettle is heated to 110-130℃, and kept constant temperature for 3-5h; the material in the reaction kettle is taken out, filtered, dried, and the flame-retardant expandable polystyrene beads are obtained.

[0006] Preferably, the specific preparation method of the hyperbranched core-shell flame retardant comprises the following steps: S1. In an oil bath at 50-55℃, 10-15 parts of expanded graphite, 0.2-0.4 parts of stearic acid and 100-200 parts of water are added to the reaction container, stirred uniformly, then 2-3 parts of acrylamide, 2-3 parts of acrylic acid, 1-2 parts of 2-acrylamide-2-methylpropane sulfonic acid, 0.5-1 parts of sodium hydroxide, 0.05-0.1 parts of propylene glycol and 0.03-0.08 parts of pentaerythritol triallyl ether are added, stirred for 30-60 min, heated to 80-90℃ under nitrogen protection, 0.02-0.05 parts of potassium persulfate is added for polymerization reaction for 3-5h, after the reaction is completed, filtration is carried out to obtain the first shell coated material; S2. The first shell coated material in step 1 is added to a mixed solution containing 1-3 parts of diethyl methylphosphonate and 80-100 parts of methanol, stirred uniformly, 0.05-0.1 parts of azobisisobutyronitrile, 0.5-1 parts of ethylene glycol dimethacrylate and 1.0-1.5 parts of vinyl acetate are mixed, slowly added into the reaction container, stirred at a speed of 100-300 rpm for 12-18h; S3. After the reaction is completed, stop heating and cool to room temperature, add hydrochloric acid to adjust the pH to 2-4, heat the oil bath to 70-80℃, reflux for 8-10h; S4. Seal the reaction container, maintain the pressure in the container at 1.5-2MPa, heat to 120-140℃, react for 6-12h, cool to room temperature, filter and dry to obtain the hyperbranched core-shell flame retardant.

[0007] Preferably, the organic dispersant is one or a combination of two or more of hydroxyethyl cellulose, methyl cellulose, sodium methyl cellulose and carboxymethyl cellulose.

[0008] Preferably, the inorganic dispersant is one or a combination of two or more of calcium carbonate, calcium phosphate, talc and magnesium carbonate.

[0009] Preferably, the initiator is one or a combination of two or more of benzoyl peroxide, t-butyl benzene peroxide and dicumyl peroxide.

[0010] Preferably, the foaming agent is one or a combination of two or more of n-pentane, iso-pentane and neopentane.

[0011] Preferably, the expanded graphite has a particle size range of 100-500 mesh.

[0012] The present application has the following beneficial effects: 1. The present application provides a flame-retardant expandable polystyrene bead and a preparation method thereof. The preparation process is simple. The hyperbranched core-shell flame retardant is prepared by coating and hyperbranched treatment of expanded graphite. The expanded graphite and the polymer matrix have good compatibility in the polystyrene polymerization process. At the same time, the matrix material can be effectively wrapped and protected after high-temperature expansion. The final polystyrene foam material has good flame-retardant performance while maintaining high compressive strength.

[0013] 2. The hyperbranched core-shell flame retardant provided by the present application has a structure of one core and two shells. The expanded graphite is used as the core, and the shell has a layered cross-linked framework structure and a large number of active functional groups on the surface. The inner shell layer is a structural layer, and the outer shell layer is a hyperbranched cross-linked layer. The inner shell layer has diffusion and deformation capacity at high temperature, effectively wraps and protects the matrix material after expansion, prolongs the plugging time of the flame retardant to the material pores, and improves the flame-retardant effect. The outer shell layer is treated on the surface of the core-shell microspheres, so that the surface cross-linking density of the flame-retardant microspheres is greater than the central cross-linking density, which helps to form a stable and perfect structure system and enhance the compressive strength of the material.

[0014] 3. The double-layer shell structure in the hyperbranched core-shell flame retardant cooperates with each other. The inner shell layer provides basic support, and the outer shell layer is effectively cross-linked. The two cooperate with each other to produce a certain synergistic effect, so that the network structure system of the core-shell microspheres is more dense and stable, and the bonding strength and integrity of the beads during foaming can be improved, so that the compressive strength of the finally prepared material is further improved. BRIEF DESCRIPTION OF DRAWINGS

[0015] Figure 1 The comparison trend chart of the limiting oxygen index and the compressive strength of the flame-retardant expandable polystyrene beads in the examples 1-5 and the comparative examples 1-3 of the present application for preparing polystyrene foam materials. DETAILED DESCRIPTION

[0016] The present application is further described below in conjunction with examples.

[0017] The raw materials of the examples and comparative examples of the present application are ordinary commercial products unless otherwise specified.

[0018] Example 1

[0019] The raw materials were weighed by parts by weight, including 20 parts of styrene monomer, 0.22 parts of organic dispersant hydroxyethyl cellulose, 0.1 parts of inorganic dispersant calcium carbonate, 0.8 parts of foaming agent n-pentane, 4.0 parts of hyperbranched core-shell flame retardant, 0.5 parts of initiator benzoyl peroxide and 100 parts of water. The styrene monomer, hyperbranched core-shell flame retardant and deionized water were put into the reaction kettle, mixed uniformly, then half of the inorganic dispersant, half of the organic dispersant and the initiator were put in, and the material in the reaction kettle was heated to 85℃, and the polymerization reaction was carried out at this temperature for 8 hours. The remaining dispersant and foaming agent were added, and the reaction kettle was heated to 120℃, and kept constant for 4h. The material in the reaction kettle was taken out, filtered and dried to obtain the expandable polystyrene beads.

[0020] The specific preparation method of the hyperbranched core-shell flame retardant includes the following steps: S1. At 50℃ in oil bath, 12 parts of expanded graphite with particle size of 200 mesh, 0.3 parts of stearic acid and 150 parts of water were added into the reaction container, stirred uniformly, then 2.5 parts of acrylamide, 2.5 parts of acrylic acid, 1.5 parts of 2-acrylamide-2-methylpropane sulfonic acid, 0.7 parts of sodium hydroxide, 0.1 parts of propylene glycol and 0.05 parts of pentaerythritol triallyl ether were added, stirred for 30 min, heated to 85℃ under nitrogen protection, 0.03 parts of potassium persulfate was added for polymerization reaction for 4h, after the reaction was completed, filtration was carried out to obtain the first shell coated material; S2. The first shell coated material in step 1 was added into a mixed solution containing 2 parts of diethyl methylphosphonate and 100 parts of methanol, stirred uniformly, 0.08 parts of azobisisobutyronitrile, 0.8 parts of ethylene glycol dimethacrylate and 1.2 parts of vinyl acetate were mixed, slowly added into the reaction container, stirred at a speed of 200 rpm for 15h; S3. After the reaction was completed, the heating was stopped and cooled to room temperature, hydrochloric acid was added to adjust the pH to 2-4, the oil bath was heated to 75℃, and the reflux reaction was carried out for 10h; S4. The reaction container was sealed, the pressure in the container was maintained at 1.5MPa, heated to 130℃, reacted for 10h, cooled to room temperature, filtered and dried to obtain the hyperbranched core-shell flame retardant.

[0021] Example 2

[0022] The raw materials are weighed by parts, including 20 parts of styrene monomer, 0.20 parts of organic dispersant methyl cellulose, 0.05 parts of inorganic dispersant calcium phosphate, 0.75 parts of foaming agent isopentane, 3.8 parts of hyperbranched core-shell flame retardant, 0.4 initiator tert-butyl benzene acid peroxide and 90 parts of water. The styrene monomer, hyperbranched core-shell flame retardant and deionized water are put into the reaction kettle, mixed uniformly, then half of the inorganic dispersant, half of the organic dispersant and the initiator are put in, and the material in the reaction kettle is heated to 80℃, and the polymerization reaction is carried out for 10 hours at this temperature. The remaining dispersant and foaming agent are added, the reaction kettle is heated to 110℃, and the temperature is kept for 5h. The material in the reaction kettle is taken out, filtered and dried to obtain the flame-retardant expandable polystyrene beads.

[0023] The specific preparation method of the hyperbranched core-shell flame retardant includes the following steps: S1. In an oil bath at 50℃, 10 parts of expanded graphite with a particle size of 100 mesh, 0.2 parts of stearic acid and 100 parts of water are added into the reaction container, stirred uniformly, then 2 parts of acrylamide, 2 parts of acrylic acid, 1 part of 2-acrylamide-2-methylpropane sulfonic acid, 0.5 parts of sodium hydroxide, 0.05 parts of propylene glycol and 0.03 parts of pentaerythritol triallyl ether are added, stirred for 30 min, heated to 80℃ under nitrogen protection, 0.02 parts of potassium persulfate are added for polymerization reaction for 3h, after the reaction is completed, filtration is carried out to obtain the first shell coated material; S2. The first shell coated material in step 1 is added into a mixed solution containing 1 part of diethyl methylphosphonate and 80 parts of methanol, stirred uniformly, 0.05 parts of azobisisobutyronitrile, 0.5 parts of dimethyl acrylate and 1 part of vinyl acetate are mixed, slowly added into the reaction container, stirred at a speed of 100rpm for 12h; S3. After the reaction is completed, the heating is stopped and cooled to room temperature, hydrochloric acid is added to adjust the pH to 2, the oil bath is heated to 70℃, and the reflux reaction is carried out for 10h; S4. The reaction container is sealed, the pressure in the container is maintained at 1.5MPa, heated to 120℃, reacted for 12h, cooled to room temperature, filtered and dried to obtain the hyperbranched core-shell flame retardant.

[0024] Example 3

[0025] The raw materials are weighed by parts, including 20 parts of styrene monomer, 0.25 parts of organic dispersant sodium methyl cellulose, 0.15 parts of inorganic dispersant talc, 0.85 parts of foaming agent neopentane, 4.2 parts of hyperbranched core-shell flame retardant, 0.6 parts of initiator dicumyl peroxide and 110 parts of water. The styrene monomer, hyperbranched core-shell flame retardant and deionized water are put into the reaction kettle, mixed uniformly, then half of the inorganic dispersant, half of the organic dispersant and the initiator are put in, and the material in the reaction kettle is heated to 90℃, and the polymerization reaction is carried out at this temperature for 6 hours. The remaining dispersant and foaming agent are added, the reaction kettle is heated to 130℃, and the temperature is kept for 3h. The material in the reaction kettle is taken out, filtered and dried to obtain the flame-retardant expandable polystyrene beads.

[0026] The specific preparation method of the hyperbranched core-shell flame retardant includes the following steps: S1. In an oil bath at 55℃, 15 parts of expanded graphite with a particle size of 500 mesh, 0.4 parts of stearic acid and 200 parts of water are added into the reaction container, stirred uniformly, then 3 parts of acrylamide, 3 parts of acrylic acid, 2 parts of 2-acrylamide-2-methylpropane sulfonic acid, 1 part of sodium hydroxide, 0.1 part of propylene glycol and 0.08 part of pentaerythritol triallyl ether are added, stirred for 60 min, heated to 90℃ under nitrogen protection, 0.05 parts of potassium persulfate are added for polymerization reaction for 5h, after the reaction is completed, filtration is carried out to obtain the first shell coated material; S2. The first shell coated material in step 1 is added into a mixed solution containing 3 parts of diethyl methylphosphonate and 100 parts of methanol, stirred uniformly, 0.1 parts of azobisisobutyronitrile, 1 parts of dimethyl glycol acrylate and 1.5 parts of vinyl acetate are mixed, slowly added into the reaction container, stirred at a speed of 300 rpm for 12h; S3. After the reaction is completed, the heating is stopped and cooled to room temperature, hydrochloric acid is added to adjust the pH to 4, the oil bath is heated to 80℃, and the reflux reaction is carried out for 8h; S4. The reaction container is sealed, the pressure in the container is maintained at 2MPa, heated to 140℃, reacted for 6h, cooled to room temperature, filtered and dried to obtain the hyperbranched core-shell flame retardant.

[0027] Example 4

[0028] The raw materials are weighed by parts, including 20 parts of styrene monomer, 0.20 parts of organic dispersant carboxymethyl cellulose, 0.1 parts of inorganic dispersant magnesium carbonate, 0.85 parts of foaming agent n-pentane, 3.8 parts of hyperbranched core-shell flame retardant, 0.6 parts of initiator tert-butyl benzene acid peroxide and 90 parts of water. The styrene monomer, hyperbranched core-shell flame retardant and deionized water are put into the reaction kettle, mixed uniformly, and then half of the inorganic dispersant, half of the organic dispersant and the initiator are put in, and mechanically stirred for 60 min. The temperature of the material in the reaction kettle is raised to 80℃, and the polymerization reaction is carried out at this temperature for 10 hours. The remaining dispersant and foaming agent are added, and the reaction kettle is heated to 130℃ and kept at this temperature for 3h. The material in the reaction kettle is taken out, filtered and dried to obtain the flame-retardant expandable polystyrene beads.

[0029] The specific preparation method of the hyperbranched core-shell flame retardant includes the following steps: S1. In an oil bath at 55℃, 12 parts of expanded graphite with a particle size of 100 mesh, 0.4 parts of stearic acid and 100 parts of water are added into the reaction container, stirred uniformly, then 2 parts of acrylamide, 2 parts of acrylic acid, 1 part of 2-acrylamide-2-methylpropane sulfonic acid, 1 part of sodium hydroxide, 0.1 part of propylene glycol and 0.03 part of pentaerythritol triallyl ether are added, stirred for 60 min, heated to 80℃ under nitrogen protection, 0.05 parts of potassium persulfate are added for polymerization reaction for 3h, after the reaction is completed, filtration is carried out to obtain the first shell coated material; S2. The first shell coated material in step 1 is added into a mixed solution containing 3 parts of methyl phosphonate diethyl and 100 parts of methanol, stirred uniformly, 0.05 parts of azobisisobutyronitrile, 1 part of dimethyl acrylate and 1.5 parts of vinyl acetate are mixed, slowly added into the reaction container, stirred at a speed of 300 rpm for 12h; S3. After the reaction is completed, stop heating and cool to room temperature, add hydrochloric acid to adjust the pH to 2, heat the oil bath to 75℃, reflux for 8h; S4. Seal the reaction container, maintain the pressure in the container at 1.5MPa, heat to 120℃, react for 12h, cool to room temperature, filter and dry to obtain the hyperbranched core-shell flame retardant.

[0030] Example 5

[0031] The raw materials are weighed by parts, including 20 parts of styrene monomer, 0.25 parts of organic dispersant hydroxyethyl cellulose, 0.15 parts of inorganic dispersant calcium carbonate, 0.85 parts of foaming agent isopentane, 4 parts of hyperbranched core-shell flame retardant, 0.4 parts of initiator tert-butyl benzene peroxide and 100 parts of water. The styrene monomer, hyperbranched core-shell flame retardant and deionized water are put into the reaction kettle, mixed uniformly, then half of the inorganic dispersant, half of the organic dispersant and the initiator are put in, and the material in the reaction kettle is heated to 80℃, and the polymerization reaction is carried out for 10 hours at this temperature. The remaining dispersant and foaming agent are added, and the reaction kettle is heated to 120℃ and kept for 4h. The material in the reaction kettle is taken out, filtered and dried to obtain the flame-retardant expandable polystyrene beads.

[0032] The specific preparation method of the hyperbranched core-shell flame retardant includes the following steps: S1. In an oil bath at 50℃, 12 parts of expanded graphite with a particle size of 500 mesh, 0.2 parts of stearic acid and 150 parts of water are added into the reaction container, stirred uniformly, then 3 parts of acrylamide, 3 parts of acrylic acid, 1 part of 2-acrylamide-2-methylpropane sulfonic acid, 0.5 parts of sodium hydroxide, 0.05 parts of propylene glycol and 0.05 parts of pentaerythritol triallyl ether are added, stirred for 60 min, heated to 85℃ under nitrogen protection, and 0.05 parts of potassium persulfate is added for polymerization reaction for 4h. After the reaction is completed, filtration is carried out to obtain the first shell coated material; S2. The first shell coated material in step 1 is added into a mixed solution containing 3 parts of diethyl methylphosphonate and 80 parts of methanol, stirred uniformly, and 0.1 parts of azobisisobutyronitrile, 0.5 parts of dimethyl ethylene glycol acrylate and 1 part of vinyl acetate are mixed, slowly added into the reaction container, and stirred at a speed of 200 rpm for 12h; S3. After the reaction is completed, stop heating and cool to room temperature, add hydrochloric acid to adjust the pH to 3, heat the oil bath to 80℃, and reflux for 8h; S4. Seal the reaction container, maintain the pressure in the container at 2MPa, heat to 120℃, react for 10h, cool to room temperature, filter and dry to obtain the hyperbranched core-shell flame retardant.

[0033] Comparative Example 1

[0034] The difference between this comparative example and Example 1 is only that in the preparation of the hyperbranched core-shell flame retardant, the inner shell layer is not coated, which includes the following steps: S1. In an oil bath at 50°C, 12 parts of expanded graphite with a particle size of 200 mesh, 0.3 parts of stearic acid, and 150 parts of water were added to a reaction vessel, stirred for 30 min, heated to 85°C under nitrogen protection, and 0.03 parts of potassium persulfate were added for polymerization for 4 h. After the reaction was completed, filtration was performed to obtain a primary shell coating material; S2. The primary shell coating material in step 1 was added to a mixed solution containing 2 parts of methyl diethyl phosphate and 100 parts of methanol, stirred uniformly, and 0.08 parts of azobisisobutyronitrile, 0.8 parts of ethylene glycol dimethacrylate, and 1.2 parts of vinyl acetate were mixed under nitrogen protection, slowly added into the reaction vessel, and stirred at a rate of 200 rpm for 15 h; S3. After the reaction was completed, heating was stopped and cooled to room temperature, hydrochloric acid was added to adjust the pH to 2-4, the oil bath was warmed to 75°C, and refluxed for 10 h; S4. The reaction vessel was sealed, the pressure in the vessel was maintained at 1.5 MPa, warmed to 130°C, reacted for 10 h, cooled to room temperature, filtered, and dried to obtain a hyperbranched core-shell flame retardant.

[0035] Comparative Example 2

[0036] The difference between this comparative example and Example 1 is that no outer shell coating was performed in the preparation of the hyperbranched core-shell flame retardant, which specifically includes the following steps: S1. In an oil bath at 50°C, 12 parts of expanded graphite with a particle size of 200 mesh, 0.3 parts of stearic acid, and 150 parts of water were added to a reaction vessel, stirred uniformly, and 2.5 parts of acrylamide, 2.5 parts of acrylic acid, 1.5 parts of 2-acrylamide-2-methylpropane sulfonic acid, 0.7 parts of sodium hydroxide, 0.1 parts of propylene glycol, and 0.05 parts of pentaerythritol triallyl ether were added, stirred for 30 min, heated to 85°C under nitrogen protection, and 0.03 parts of potassium persulfate were added for polymerization for 4 h. After the reaction was completed, filtration was performed to obtain a primary shell coating material; S2. The primary shell coating material in step 1 was added to 100 parts of methanol, stirred uniformly, and stirred at a rate of 200 rpm for 15 h under nitrogen protection; S3. After the reaction was completed, heating was stopped and cooled to room temperature, hydrochloric acid was added to adjust the pH to 2-4, the oil bath was warmed to 75°C, and refluxed for 10 h; S4. The reaction vessel was sealed, the pressure in the vessel was maintained at 1.5 MPa, warmed to 130°C, reacted for 10 h, cooled to room temperature, filtered, and dried to obtain a hyperbranched core-shell flame retardant.

[0037] Comparative Example 3

[0038] The difference between the present comparative example and Example 1 is that the preparation of the flame-retardant expandable polystyrene beads is only replaced by the ordinary expanded graphite instead of the hyperbranched core-shell flame retardant.

[0039] Effect demonstration

[0040] The flame-retardant expandable polystyrene beads obtained in the examples and comparative examples are filled into a mold, the temperature is controlled at 110℃, and then the mold is pressed and foamed to form polystyrene foaming materials. The foaming materials are determined for compression strength according to GB / T 8813-2008 "Hard Foam Plastic Compression Strength Test Method", and the limiting oxygen index is tested according to GB / T 2406.2-2009 "Oxygen Index Method for Determining Combustion Behavior of Plastics". The specific test results are shown in Table 1:

[0041] Result analysis

[0042] The examples 1-5 and comparative examples 1-3 are analyzed, combined with the data in Table 1 and Figure 1 It can be seen that the polystyrene foaming material prepared by the flame-retardant expandable polystyrene beads provided by the present application has good flame-retardant performance, and at the same time has high compression strength, and the specific analysis is as follows: As can be seen from Comparative Example 1, when the inner shell layer is not coated in the preparation of the hyperbranched core-shell flame retardant, the limiting oxygen index of the polystyrene foaming material prepared is obviously decreased, and the flame-retardant performance is greatly reduced; As can be seen from Comparative Example 2, when the outer shell layer is not coated in the preparation of the hyperbranched core-shell flame retardant, the compression strength of the polystyrene foaming material prepared is obviously decreased, and the mechanical property is greatly reduced; In summary, from Comparative Examples 1-3, it can be seen that the inner shell layer of the hyperbranched core-shell flame retardant can improve the flame-retardant performance of the polystyrene foaming material, the outer shell layer can improve the compression strength of the polystyrene foaming material, and at the same time, the inner and outer shell layer structures can cooperate with each other to produce a certain synergistic effect, so that the compression strength of the foaming material is further improved.

[0043] In addition, it should be noted that each specific technical feature described in the above specific embodiments can be combined in any appropriate manner without contradiction, and in order to avoid unnecessary repetition, the present application will not further describe various possible combinations.

[0044] In addition, various different embodiments of the present application can also be combined in any manner, as long as they do not deviate from the idea of the present application, and they should also be considered as disclosed by the present application.

Claims

1. A flame-retardant expandable polystyrene bead, characterized in that, The product is prepared from the following raw materials in parts by weight: 20 parts styrene monomer, 0.20-0.25 parts organic dispersant, 0.05-0.15 parts inorganic dispersant, 0.75-0.85 parts foaming agent, 3.8-4.2 parts hyperbranched core-shell flame retardant, 0.4-0.6 parts initiator, and 90-110 parts water, wherein the hyperbranched core-shell flame retardant is prepared by encapsulating expanded graphite in a shell and hyperbranching process.

2. The flame-retardant expandable polystyrene beads according to claim 1, characterized in that, The specific preparation method of the hyperbranched core-shell flame retardant includes the following steps: S1. By weight, in an oil bath at 50-55℃, add 10-15 parts expanded graphite, 0.2-0.4 parts stearic acid and 100-200 parts water to the reaction vessel. After stirring evenly, add 2-3 parts acrylamide, 2-3 parts acrylic acid, 1-2 parts 2-acrylamido-2-methylpropanesulfonic acid, 0.5-1.0 parts sodium hydroxide, 0.05-0.1 parts propylene glycol and 0.03-0.08 parts pentaerythritol triallyl ether. Stir for 30-60 minutes. Under nitrogen protection, heat to 80-90℃ and add 0.02-0.05 parts potassium persulfate to carry out the polymerization reaction for 3-5 hours. After the reaction is completed, filter to obtain the primary shell-coated material. S2. Add the shell coating material from step 1 to a mixed solution containing 1-3 parts diethyl methyl phosphate and 80-100 parts methanol, stir until homogeneous, and under nitrogen protection, mix 0.05-0.1 parts azobisisobutyronitrile, 0.5-1 parts ethylene glycol dimethacrylate and 1.0-1.5 parts vinyl acetate, and slowly add the mixture dropwise into the reaction vessel, stirring at a rate of 100-300 rpm for 12-18 hours; S3. After the reaction is complete, stop heating and cool to room temperature. Add hydrochloric acid to adjust the pH to 2-4, heat the oil bath to 70-80℃, and reflux for 8-10 hours. S4. Seal the reaction vessel, maintain the pressure inside the vessel at 1.5-2.0 MPa, heat to 120-140℃ and react for 6-12 hours, cool to room temperature, filter, and dry to obtain a hyperbranched core-shell flame retardant.

3. The flame-retardant expandable polystyrene beads according to claim 1, characterized in that, The organic dispersant is one or a combination of two or more of hydroxyethyl cellulose, methyl cellulose, sodium methyl cellulose and carboxymethyl cellulose.

4. The flame-retardant expandable polystyrene beads according to claim 1, characterized in that, The inorganic dispersant is one or a combination of two or more of calcium carbonate, calcium phosphate, talc, and magnesium carbonate.

5. The flame-retardant expandable polystyrene beads according to claim 1, characterized in that, The initiator is one or a combination of two or more of benzoyl peroxide, tert-butyl benzoate peroxide, and dicumyl peroxide.

6. The flame-retardant expandable polystyrene beads according to claim 1, characterized in that, The foaming agent is one or a combination of two or more of n-pentane, isopentane, and neopentane.

7. The flame-retardant expandable polystyrene beads according to claim 1, characterized in that, The expanded graphite has a particle size range of 100-500 mesh.

8. A method for preparing flame-retardant expandable polystyrene beads, characterized in that, The preparation of the flame-retardant expandable polystyrene beads according to any one of claims 1-7 specifically includes the following steps: Weigh out the raw materials, add styrene monomer, hyperbranched core-shell flame retardant and deionized water into the reactor, mix evenly, then add half of the inorganic dispersant, half of the organic dispersant and initiator, and mechanically stir for 30-60 minutes. Raise the temperature of the material in the reactor to 80-90℃, and polymerize at this temperature for 6-10 hours. Add the remaining dispersant and foaming agent, heat the reactor to 110-130℃, and maintain the temperature for 3-5 hours. Take out the material in the reactor, filter, and dry to obtain flame-retardant expandable polystyrene beads.

Citation Information

Patent Citations

  • Preparation method for flame retardant expanded polystyrene with core-shell structure

    CN104072691A

  • Halogen-free flame retardant namely expandable polystyrene particle and preparation method thereof

    CN110804203A

  • Flame-retardant acrylic pressure-sensitive adhesive and preparation method thereof

    CN114774034A